(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Fundamental analysis is stock valuation method used to find the financial healthiness of the company by analysing the impact of macroeconomic variables on stock market, considering the various trends, opportunities, challenges of the industry in which the company operates and assessing the projected performance of the company. This study not only restricted to financials but also focused on other Qualitative factors of the company.The study selected four automobile companies viz., Ashok Leyland, Tata motors, Mahindra Mahindra and Force motors and analysed their financial data from 2015-19 with help of various financial ratios and finally selected Mahindra Mahindra for conducting fundamental analysis. The study considered variables like Earnings Multiples, Growth, EPS etc.